An imperative to cure : principles and practice of Qʼeqchiʼ Maya medicine in Belize - Waldram, James B. (James Burgess) (University of New Mexico Press, 2020)
"James B. Waldram's groundbreaking study, an imperative to cure: principles and practice of Qʼeqchiʼ Maya medicine in Belize, explores how our understanding of indigenous therapeutics changes if we view them as forms of "medicine" instead of "healing." Bringing an innovative methodological approach based on fifteen years of ethnographic research, Waldram argues that Qʼeqchiʼ medical practitioners access an extensive body of empirical knowledge and personal clinical experience to diagnose, treat, and cure patients according to a coherent ontology and set of therapeutic principles. Not content to leave the elements of Qʼeqchiʼ cosmovision to the realm of the imaginary and beyond human reach, Qʼeqchiʼ practitioners conceptualize the world as essentially material and meta/material, consisting of complex but knowable forces that impact health and well-being in real and meaningful ways-forces with which Qʼeqchiʼ practitioners must engage to cure their patients"--